Finite-dimensional Chu space - Nhụy, Nguyễn (Journal of Computer Science and Cybernetics, 2016)
In this note we introduce the notion of finite-dimensional space and extend a result in [3] stating that, every fully complete Chu space is a fuzzy space. Finally, the general results are applied to a concrete example of theory of game.